Education and urbanization improves cognitive function affected by altitude of adolescents: a cross-section study in Tibet, China - Yangzong Ciren; Jianhong Gong; Furong Li; Xiaofeng Gong; Dunzhu Danzeng; Yanping Ning; Tianheng Wang; Xiaobing Tian; Quzha Silang (Frontiers in Public Health)
BackgroundThe aim of the study was to examine the cognitive function of Tibetan adolescents at different altitudes and evaluate the influence of education and urbanization on child’s cognition at high altitudes.MethodsA cross-sectional study was conducted between October 2015 and September 2016 in four counties in Tibet. The study population included 324 adolescents living at an altitude of 2,800 m, including 227 who grew up at altitudes of 4,300 m, and 732 adolescents attending three high-altitude boarding schools (one at 4,300 m and two at 4,500 m), including 119 who grew up at an altitude of 2,800 m. Fluid reasoning was assessed using Standard Progressive Matrices (SPMs). The background information was collected using self-administered questionnaires.ResultsA multilevel linear regression model was used to determine the effects of altitude, education, and urbanization on fluid reasoning. In the fixed-effects model, the average SPM score of adolescents from low altitudes who attended kindergarten was 40.41. Scores of students who moved from high to low altitudes, came from high altitudes, and moved from low to high altitudes were 2.66, 4.71, and 6.70 points lower, respectively, than those of students from low altitudes, and 2.50 points lower in students who had not attended kindergarten than those who had. In the random-effects model, the scores of those who only went to first grade were 2.93 points lower. Students from County 3 had average scores of 1.89 higher than did students from the other three counties.ConclusionHigh altitudes may negatively affect the cognition of Tibetan adolescents. This effect was reduced by moving to a lower altitude, increasing the number of years of formal education, attending kindergarten, and living in a more urbanized location. Even at high altitude, moving to higher altitudes should be avoided.